(untitled) (Estudios Sociales, 2021)
With the coup of september 6, 1930, a new federal intervention arrived in Mendoza, led by the nationalist José María Rosa (son). His term extended until february 1932, when the democrat candidate Ricardo Videla took office. Both governments sought to restrict the political participation and electoral chances of the «Unión Cívica Radical Lencinista», and also restricted the action of other «radical» political groups. This paper seeks to analyze the mechanisms used by both governments to restrict the political actions of the «Lencinist» party and reconstruct what was the response of said party. The aim is to relativize the use of electoral fraud in the different elections of the period, with respect to other institutional breakdowns and legal arguments used by the governments of these years, and also the appeal to other types of parastatal restrictions, such as political violence.